(untitled) (Medico Legal Update, 2021)
Background and Aims: Incidence of Postoperative (Postop) Acute Kidney Injury (AKI) and related comorbidities can be prevented by identifying various preoperative and intraoperative predictors in the patients. Early recognition of risk factors and timely intervention can reduce morbidity and mortality related to AKI in a patient with preoperative normal renal function . Method: This prospective observational cohort study was done in 100 patients undergoing major noncardiac surgery under spinal, epidural or general anaesthesia, who were having normal preoperative renal function. Intraoperative predictors of AKI monitored were bloodloss, hypotension, duration of surgery, volume of fuid infused, urine output (UOP), use of vasopressor and diuretics. Postoperatively urine output and serum creatinine level were noted for 3 days. Postoperative AKI was defined and classified as per RIFLE criteria. Results: Total 33% patients were diagnosed to have Postop AKI and the major risk factors identified were duration of surgery, volume of fluid given intraoperatively, blood loss and UOP postoperatively (p value <0.001). Non significant risk factors were demographic data, mode of anaesthesia given, diuretic usage, drug therapy. Conclusion: We concluded in our study that in patient with preoperative normal renal function undergoing noncardiac surgery various predictors for AKI can be identified early and optimised for better outcome. These factors are duration of surgery, blood loss, volume of fluid infused.